Achieving meaningful participation of people who use drugs and their peer organizations in a strategic research partnership - Graham Brown; Sione Crawford; Gari-Emma Perry; Jude Byrne; James Dunne; Daniel Reeders; Angela Corry; Jane Dicka; Hunter Morgan; Sam Jones (BMC, 2019)
Abstract Background Peer-led programs with people who use drugs (PWUD) have been a key characteristic of the harm reduction in many countries, including their involvement in research. However, peer involvement in research is often limited to recruitment, consultation, and reporting back, rather than a genuine collaboration in the priority setting, design, and conduct of research. PWUD peer organizations face ongoing challenges to demonstrate the depth of their knowledge of current and emerging issues within drug-using networks and the value of their peer insights for effective research and policy. The identification of benefits, barriers, and enablers for meaningful participation of PWUD in research has often been limited to methodological rather than system level factors. Methods This paper draws on the experiences and findings of the What Works and Why (W3) Project, a 5-year collaborative study with peer organizations. The study drew on systems thinking methods to develop a framework to demonstrate the role of peer organizations within their community and policy systems. The study required peer staff and researchers to undertake the simultaneous role of drivers, participants, and analysts in the research. To identify the learnings in relation to meaningful participation of PWUD peer organizations in research, we drew together the insights and experiences of peer staff and researchers across the 5 years of the study Results The W3 Project provided insights into the nuances of community-engaged research practice and the ongoing benefits, barriers, and enablers to the meaningful participation of PWUD and their peer organizations. These included system-level barriers and enablers beyond individual research projects or methodology. The capacity of research and peer organizations to maintain meaningful peer participation in research can be restricted or enhanced by the systems in which they are embedded. Conclusions Recognizing peer organizations as active participants and drivers within community and policy systems can help clarify their unique and critical role in research. Achieving meaningful collaboration with PWUD peer organizations requires looking beyond good practice methods to the system-level factors with attention to the system-level benefits, barriers, and enablers.